2022
DOI: 10.1155/2022/1526217
|View full text |Cite
|
Sign up to set email alerts
|

Advance of Mesenchymal Stem Cells in Chronic End-Stage Liver Disease Control

Abstract: The chronic liver diseases will slowly develop into liver fibrosis, cirrhosis, and even liver cancer if no proper control is performed with high efficiency. Up to now, the most effective treatment for end-stage liver diseases is liver transplantation. However, liver transplantation has the problems of donor deficiency, low matching rate, surgical complications, high cost, and immune rejection. These problems indicate that novel therapeutic strategies are urgently required. Mesenchymal stem cells (MSCs) are som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 171 publications
0
6
0
1
Order By: Relevance
“…In the current study, we like to assess if curcumin preconditioning of MSCs can maintain this ameliorative effect and protect against return of the fibrosis which actually represent a critical challenge in use MSCs in therapy and still there is a controversy about the long term efficacy of stem cells, there many preclinical and clinical studies prove the reduction of liver fibrosis by MSCs injection [24][25][26] but maintaining its effect were achieved after many times of cell injection up to 9 injections in one experiment [27] and partially achieved in another studies [28][29] and not achieved at all in others [30][31]. So, we investigated the fibrosis degree on 12 th week and 24 th week of cell infusion and we found that no significant difference compared to that at 4 th week in cur + /nanoscaffold and this indicates that curcumin preconditioning of MSCs maintained the ameliorative effect of the primed MSCs and protected against the return of fibrosis compared to cur -/nanoscaffold which showed a return of fibrosis from 6.5% to 10.4% .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we like to assess if curcumin preconditioning of MSCs can maintain this ameliorative effect and protect against return of the fibrosis which actually represent a critical challenge in use MSCs in therapy and still there is a controversy about the long term efficacy of stem cells, there many preclinical and clinical studies prove the reduction of liver fibrosis by MSCs injection [24][25][26] but maintaining its effect were achieved after many times of cell injection up to 9 injections in one experiment [27] and partially achieved in another studies [28][29] and not achieved at all in others [30][31]. So, we investigated the fibrosis degree on 12 th week and 24 th week of cell infusion and we found that no significant difference compared to that at 4 th week in cur + /nanoscaffold and this indicates that curcumin preconditioning of MSCs maintained the ameliorative effect of the primed MSCs and protected against the return of fibrosis compared to cur -/nanoscaffold which showed a return of fibrosis from 6.5% to 10.4% .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles are prepared by subjecting MSCs to serial extrusion through filters with diminishing pore sizes. MSCs have immunomodulatory potential and low immunogenicity [18,19]. Both MSCs and MDSCs are closely related to immune function, within which there may be a natural targeting between them.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic liver diseases slowly develop into end‐stage liver diseases if not controlled properly and promptly. Currently, the most effective treatment for end‐stage liver diseases is liver transplantation 1 . However, alternative treatment strategies are needed as insufficient donor sources, post‐transplant rejection, and high treatment costs limit the applicability of liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2 million people die every year from liver diseases worldwide, accounting for 3.5% of all deaths. 1 Chronic liver diseases slowly develop into end-stage liver diseases if not controlled properly and promptly. Currently, the most effective treatment for end-stage liver diseases is liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation